Correction to: Exploring effects of supplementary cementitious materials on setting time, strength, and microscale properties of mortar (Discover Applied Sciences, (2024), 6, 11, (583), 10.1007/s42452-024-06180-x) - Romero, Lenin Miguel Bendezu (2024)
In this article some of the authors’ details were incorrectly published, as listed below. The fifth author’s family name, Velarde, was incorrectly written as Valarde, and the author’s affiliation was incorrectly specified as ‘Department of Civil Engineering, Universidad Peruana de Ciencias Aplicadas, Lima, Peru’. It should be ‘Department of Civil Engineering, Universidad César Vallejo, Lima, Peru’. The fourth author’s affiliation was incorrectly specified as ‘Department of Civil Engineering, Prince Mohammad Bin Fahd University, Al Khobar, Saudi Arabia’. It should be ‘Department of Civil Engineering, Covenant University, Ota, Ogun State, Nigeria’. The last author’s email address (k.prakash@utem.cl) was missing. The original article has been corrected.